PENGARUH MOTIVASI TERHADAP MINAT MAHASISWA UNTUK MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI (Studi Empiris pada Mahasiswa Akuntansi Universitas Brawijaya) - Yudhistira Bayu Perkasa; Made Sudarma (Jurnal Ilmiah Mahasiswa FEB, 2013)
This research aimed to analyze and provide empirical evidence about the effect of motivation on student interest in accounting to follow an Accounting Profession Education in Brawijaya University. The variabels used are quality motivation, career motivation, economic motivation, and social motivation. The population in this research is a student majoring in Accounting S1 2010 which isstill active in the Brawijaya University. Samples used in this research is 67 respondents.The research data used primary data obtained from questionnaire. The analytical method used to test hypothesis in this research is multiple regression analysis method. The data have been obtained are then analyzed using SPSS version 17.0.The results of this research shows that the quality motivation, career motivation, and social motivation have significant influence toward the interest of accounting students to follow an Accounting Profession Education. While economic motivation has no significant influence toward interest of accounting students to follow an Accounting Profession Education. Keywords : Quality Motivation, Career Motivation, Economic Motivation,Social Motivation, Interest, Accounting Profession Education